Audiographic system and its application - Kader Mastan, Zoorina Bee; Ahmad, Zainal Abidin (Penerbit UTM Press, 1993)
In enhancing the telephone service, audiographic system has been identified as the potential added value system. This paper describes the importance of audiographic system, system concept and feasible application areas.